The monetary policy of inflation targeting as a nominal anchor: The Ghanaian experience - Dahalan, Jauhari; Umar, Mohammed (2015)
The paper examines whether the Ghanaian Inflation Targeting (IT) framework has performed the role of the nominal anchor in the economy or not as well as the process through which the monetary authority determines the monetary instrument - interest rate, in the economy.Using the Generalized Method of Moments (GMM) estimators, the baseline and augmented forward looking monetary policy rules were estimated for the pre, post-IT adoption and full sample periods.The findings vary across regimes.The result prior to the adoption of the IT framework does not follow the IT principle, whereas that of the post IT adoption and full sample periods is characterized as a forward-looking IT framework.The paper further uses the augmented monetary policy rule to identify the factors that determine the monetary policy instrument in the economy.The result confirms that the Ghanaian monetary economy practice full pledge IT principle immediately after the adoption of the IT framework and that the monetary policy rule serve as a nominal anchor for the Ghanaian economy.